Антология выдающихся достижений в науке и технике. Часть 28: Портреты легендарных физиков "высоковольтной бригады" УФТИ - Баранов, М.И. (Електротехніка і електромеханіка, 2015)
Приведен научно-исторический очерк об известных харьковских физиках, входивших в состав знаменитой «высоковольтной бригады» Украинского физико-технического института, первыми в СССР расщепивших искусственно ускоренными в высоковольтном генераторе с электроразрядной трубкой протонами на энергию до 350 кэВ ядро атома
лития и достигших в недалеком будущем своих научных академических вершин и новых научно-технических свершений в области ядерной физики и физики высоких энергий. Наведено науково-історичний нарис про відомих харківських фізиках, що входили до складу знаменитої «високовольтної бригади» Українського фізико-технічного інституту, що першими в СРСР розщепнули штучно прискореними в
високовольтному генераторі з електророзрядною трубкою протонами на енергію до 350 кэВ ядро атома літію і що
досягли в недалекому майбутньому своїх наукових академічних вершин і нових науково-технічних звершень в галузі
ядерної фізики і фізики високих енергій. Purpose. Description of the basic distinguished scientific
achievements of members of «high-voltage brigade» of the
Ukrainian Physical-Technical Institute (UPhTI) and future Academicians in area of nuclear physics − Valter A.C., Sinelnikov
C.D., Leypunskiy A.I. and Latyshev G.D. Methodology. Scientific approaches at treatment and systematization of physical
knowledges. Historical method at research of development in
Ukraine and Russia of nuclear physics and mastering of intranuclear energy for military and peaceful aims. Results. The
basic creative and vital stages, and also prominent scientific
results, obtained by the indicated scientists in the area of nuclear physics, physics of high energies and nuclear energy, are
resulted in the compressed and systematized way. Some technical descriptions created by these Kharkov physicists of powerful
high-voltage electrostatic and linear dynamitrons and protons,
and also nuclear reactors fast-neutron are indicated. Originality. Firstly in the area of history of scientific-technological authoritative enough scientist-electro-physicist, which is engaged
not alone ten of years by creation of powerful generators of very
high voltage and large currents, and also presents a theoretical
electrophysics a wide reader a scientifically-historical essay
with not popular details about the first in the USSR breaking up
the physicists of UPhTI of atomic kernel of lithium by artificially
speed-up protons. Firstly the basic distinguished scientific
achievements of the considered physicists-nuclear engineers are
resulted in the concentrated way. Practical value. Scientific
popularization of physical knowledges and achievements of the
known compatriots, bringing in a big contribution to development of nuclear physics, physicists of high energies and nuclear
energy.